ANALISIS PERANAN COST-CONTROLLER TERHADAP SISTEM PENGENDALIAN INTERN ATAS PERSEDIAAN PADA HOTEL KAPUAS PALACE DI PONTIANAK - Louw, Febriana (MABIS, 2012)
Inventories and supplies are very important assets in a company because of the significant value in the financial statements, the Income statement and balance sheet can not be drawn without knowing the value of inventories. Errors in inventories count will directly result in an error in financial statements. However, inventories and supplies are also significant value in service companies, such as Kapuas Palace Hotel. The study was done in order to determine the factors that cause inventory inaccuracy with the amount of physical in the warehouse, and the weaknesses of inventory control system that have been implemented by the cost - controller Kapuas Palace Hotel. The study will focus on the issues that activities occur in the Kapuas Palace Hotel implemented cost controller, which includes the activities of goods "in and outâ each day, as well as supervision of employees. The results of research find some drawbacks such as the organizational structure is not clearly functionally separate, setting the location of the goods or supplies in warehouses that are less organized and less attention, and manual recording is still less effective and efficient since the resulting errors tend to be high. The suggestions are given to minimize errors and assist the progress of the system is to control the activities of inventories, warehouse employees should check the goods are shipped to more carefully and do not sign the purchase invoice prior to finished goods inspected.